Saskia Boelsums kunstenaar met een camera = artist with a camera - Boelsums, Saskia 1960-; Dixon, Kay (Terra, 2022)
This third book by Saskia Boelsums shows the development of the award-winning visual artist and photographer in text and image. As an artist, Boelsums was soon captivated by photography. Or actually because of the beauty of a pomegranate. Her search for how to express this special experience led to her current specialization through still life and portrait photography: painterly and impressionistic landscape photography. With many photos, different types of paper to show the art to its fullest and a personal interview, this book gives a picture of her development into the artist she is today. Exhibition: Museum JAN, Amstelveen, the Netherlands (30.6-25.9.2022)
Catalog of an exhibition held at Museum JAN, Amstelveen, Netherlands, from June 30 - September 25, 2022
Keywords: Boelsums, Saskia -- 1960-; Landschaftsfotografie; Fotografie; Boelsums, Saskia; Photography, Artistic / Exhibitions; 2000-2099; Ausstellungskatalog -- Museum JAN -- 30.06.2022-25.09.2022 -- Amstelveen; Bildband